التطور الدلالي لبعض المفردات في الحكم العطائية: دراسة دلالية وأثرها في تعليم علم الدلالة - Sukkan Arya Putra (STIT Darul Hijrah Martapura, 2025)
This study analyzes semantic development in fifteen vocabulary items from Al-Hikam al-‘Aṭā’iyyah and its implications for teaching Ilm al-Dalālah. A qualitative library-research design compares lexical meaning, Sufi contextual meaning, semantic change, and semantic-field relations. The findings identify spiritualization, internalization, value reorientation, differentiation, metaphorization, specialization, and broadening. The dominant movement redirects general meanings toward al-iftiqār ilā Allāh, or human existential dependence on God. Al-Hikam can therefore serve as an authentic text for training students to compare dictionary and contextual meanings, classify semantic change, construct semantic fields, and develop linguistic sensitivity.